Thermostabilization of Penicillium restrictum glycosidases - Borzova, Nataliia; Gudzenko, Olena (Problems of Environmental Biotechnology, 2021)
Stabilization of α-L-rhamnosidase and α-galactosidase molecules with sorbitol and glycerol solutions was studied.